(untitled) (Politeja, 2024)
THE OCTOBER 15TH 2023 PARLIAMENTARY ELECTIONS AND REFERENDUM IN POLAND: ISSUES AND CONCERNS REGARDING CONCURRENT VOTING Poland does not have much experience in holding nationwide referendums. Moreover, never before did the elections and referendums take place on the same day. Even though the simultaneous organisation of elections and referendums is not something new in the political practice of many democracies, this issue is rarely discussed in the scholarly literature. This is due to the fact that elections and referendums rarely take place concurrently. Taking into consideration that the decision to hold both events concurrently should bear in mind the efficiency of both processes, the cost of organisation, different technical and legal issues as well as the impact of the entire electoral and referendum cycle on the freedom and fairness of voting, one can see the many challenges such concurrent voting entails. In this article the authors examine the most important challenges and concerns associated with this year’s organisation of concurrent referendum and parliamentary elections in Poland on Sunday October 15th, trying to answer at the same time what is its impact on the quality of voting in the country.